Built Environment and Active Transport to School (BEATS) Study: Multidisciplinary and Multi-Sector Collaboration for Physical Activity Promotion (El estudio «Entorno construido y desplazamiento activo a la escuela (BEATS)»: colaboración multidisciplinaria - Sandra Mandic; Ashley Mountfort; Debbie Hopkins; Charlotte Flaherty; John Williams; Emily Brook; Gordon Wilson; Antoni Moore (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Abstract.  The Built Environment and Active Transport to School (BEATS) Study examines active transport to school (ATS) in adolescents in Dunedin, New Zealand, using the ecological model for active transport which accounts for individual, social, environmental, and policy influences. This article describes the BEATS Study design, the establishment of research and community collaborations, planning and preparation for data collection, study implementation and dissemination activities and selected preliminary findings. The BEATS Study is founded on a multidisciplinary approach and multi-sector collaborations between secondary schools, the city council, the local communities, and academia. The study uses a mixed-method approach incorporating both quantitative (survey) and qualitative (focus groups/interviews) approaches with students, parents, teachers and school principals. All 12 secondary schools in Dunedin, New Zealand, are participating in the study. As of September 2014, 1,272 adolescents from nine schools (age: 15.3±1.4 years; 46.6% boys) completed the student survey. Three additional schools will be surveyed in 2015. On average, 33.0% of Dunedin adolescents use ATS. ATS rates vary greatly by school (range: 8.6% to 46.5%) and most students like the way how they travel to school (88.3%). With 100% school recruitment rate, this study provides a unique sample of students and parents across one city with a heterogeneous physical environment. The findings will enable community health promoters, policy makers and city planners to address ATS barriers, encourage active transport and create supportive built environments to promote ATS.